Beneficial effects of a prescription home-prepared diet and of zucchini on urine calcium oxalate supersaturation and urinary parameters in adult cats. Issue 12 (December 2022) - Blanchard, Géraldine; Amato, Concetta; André, Agnès; Bleis, Philippe; Ninet, Samuel; Zentek, Jürgen; Nguyen, Patrick
Objectives: From the authors' experience, the consumption of a balanced prescription home-prepared diet that includes zucchini (courgette) benefits cats with recurrent urolithiasis, but there is no published evidence to support this. The aim was to study the effects on urinary parameters of (1) a balanced prescription home-prepared diet containing zucchini, and (2) the addition of zucchini to a dry food, compared with two commercial therapeutic diets. Methods: Eight healthy cats were included in a Latin-square designed protocol. Five diets were evaluated: two commercial diets, designed for cats with urinary disorders, one high-moisture (U-WET) and one high-sodium dry (U-DRY); one home-prepared diet (HOME); one commercial dry food for adult maintenance (DRY); and DRY given together with 10 g of zucchini per kg body weight (DRY-Zuc). After a 7-day adaptation period, urine was collected and daily food and water intakes were assessed for 12 days. Urinary parameters, and relative supersaturation (RSS) for calcium oxalate (CaOx) and struvite, were determined. Data underwent repeated measures ANOVA analysis. Results: The digestibility of energy, dry matter, protein and fat was highest with the HOME diet. CaOx RSS was lowest in cats eating the HOME diet, but not significantly different from the U-WET or U-DRY diets. CaOx RSS was lower in cats eating the DRY-Zuc diet than in cats eating the DRY diet. Struvite RSS did not differ significantly among groups. Conclusions and relevance: This study shows that a balanced prescription home-prepared diet was safe and allowed a very low urinary CaOx RSS. It also showed that adding zucchini to dry food lowered the urine CaOx RSS.